The Effect of Accumulation of Leaf Litters and Allelochemicals in the Soil to the Sustainability of the Newly Introduced Crop Plants - I Gede Ketut Adiputra (Universitas Gadjah Mada, 2022)
Indonesia is the second-largest vanilla production and the third-largest cocoa production in the world, but it sustained for a short period. The unsustainability of these crops is speculated to occur because of the change in leaf litter accumulation which affected the sustainability of soil organic carbon that plays an important role in maintaining soil health and fertility. To find out methods that could improve the sustainability of the production, a literature review was conducted. The articles, related to the sustainability of vanilla and cacao production, were collected using Google Scholar, Wiley Online Library, ResearchGate, and Google Chrome browser. Keywords were employed to find the articles includingsoil organic carbon, cocoa plantation, vanilla, leaf litter, and allelochemical. This current article review foundthat introducing crop by clearing of previously existing vegetation could severely reduce the rate of leaf litter accumulation. Consequently, in a prolonged period, the soil organic carbon and soil fertility are very low and are unable to support the healthy growth and production of the crops. To restore production, the plantation then is returned to more traditional agroforestry such as replanting shading trees and addition of mulch. However, in the higher density of canopy, the crop production is low attributed partly to the decreasing soil pH which increases the impact of allelochemical. This review concluded that the sustainability of leaf litter accumulation is crucial to maintain soil health, but mitigation is required to reduce the impact of allelochemical accumulation.